Sleep-Disordered Breathing and Verbal Skills in School-Aged Community Children - Honaker, Sarah Morsbach (2009)
Sleep-disordered breathing (SDB) has been repeatedly associated with neurocognitive deficits in children. However, impairments in verbal skills have been inconsistently reported. The effects of SDB on verbal skills of 76 age-, gender, ethnicity, and maternal education matched groups of children with habitual snoring, but normal overnight sleep studies (HS), and children with significant SDB were compared to non-snoring healthy controls. A multi-method assessment of verbal abilities, and language neurodevelopment was chosen to unravel verbal skills. Preschoolers' difficulties in processing verbal instructions of increasing linguistic complexity, and school-aged children's reduced ability of verbal concepts provide evidence of SDB effects on verbal abilities. Although overall cognitive performances of SBD children remain in normative range, their problematic verbal skills may ultimately adversely affect academic performances or socio-emotional behaviors.